REFORMIST TRENDS IN CORPORATE FOOD REGIME: INDONESIA’S RESPONSE TO THE FERTILIZER SUPPLY CRISIS DURING THE RUSSIA-UKRAINE WAR - Afgan Fadilla; Mujahid Widian Saragih; Faris Widiyatmoko; Winda Eka Pahla Ayuningtyas (SOSIOEDUKASI, 2025)
The Russia-Ukraine war triggered a global fertilizer supply crisis, revealing the vulnerability of import-dependent agricultural systems. This study examines Indonesia’s policy response to the fertilizer supply crisis during the 2022 Russia–Ukraine war, focusing on the expansion of subsidies for urea and Nitrogen, Phosphorus, and Potassium fertilizers. The objective is to identify how Indonesia’s policy represents a Reformist trend – one of Holt-Giménez and Shattuck’s typologies – within the corporate food regime. Using a qualitative research method, the study draws on secondary data, including policy documents, government budget reports, and statements from international organizations. The findings show that Indonesia’s policy actions exemplify the Reformist trend within the corporate food regime, in which the state seeks to manage crises and maintain political stability without transforming structural dependencies.